Pengaruh Penggunaan Media Powerpoint Intetaktif dalam Pembelajaran Matematika terhadap Prestasi Belajar Siswa Kelas VIII SMPN 1 Gunungsari Tahun Ajaran 2024/2025 - Lestari, Ayu; Sripatmi; Kurniawan, Eka; Sarjana, Ketut (FKIP Universitas Mataram, 2025)
This study aims to determine the effect of using interactive powerpoint media in mathematics learning on the academic achievement of eighth-grade students at SMPN 1 Gunungsari in the 2024/2025 academic year. This research is a quantitative study using a quasi-experimental method. The population in this study consists of eighth-grade students at SMPN 1 Gunungsari in the 2024/2025 academic year, totaling 295 students, comprising 140 male students and 156 female students, distributed across ten classes (VIII A to VIII J). The sample in this study includes class VIII G, consisting of 29 students as the control class, and class VIII J, consisting of 27 students as the experimental class, selected using cluster random sampling. Data collection techniques used in this study include observation, tests, and documentation. The data analysis techniques employed are descriptive and inferential statistics, including normality tests, homogeneity tests, t-tests, and effect size tests. Based on the t-test analysis, it was found that t_count > t_table (2.913 > 2.005) at a 5% significance level. This indicates a significant difference in academic achievement between the experimental and control groups, with the experimental group having a higher average score of 75,66 compared to the control group’s average score of 65,56. The effect size test yielded a value of d=0.78 indicating that the effect of using interactive powerpoint media falls into the medium category. Therefore, it can be concluded that the use of interactive PowerPoint media influences the mathematics learning achievement of eighth-grade students at SMPN 1 Gunungsari in the 2024/2025 academic year.